Juridical analysis of traffic accident resolution using restorative justice at the Serang City Police Station - Asnawi Asnawi; Pratiwi Aprilia Rahmawati; Aris Setyanto Pramono; Ayang Fristia Maulana (Institute Of computer Science (IOCS), 2023)
Most Indonesian people use transportation, accidents often occur on the highway, there is a lack of public awareness of traffic, which results in accidents. The public must understand and obey traffic regulations properly. This research aims to analyze or examine the legal norms and regulations of restorative justice at the Serang City Police in completing deliberations between traffic accident victims, to examine the obstacles to implementing restorative justice in traffic accident cases. In this research, which I carried out directly, I used an empirical juridical research approach, namely taking data sources using a direct approach using observations and interviews at the Serang City Police Station. and uses primary data sourced from statutory regulations, as well as data from secondary legal materials including other expert opinions, journals of several expert opinions, and tertiary legal materials. Restorative justice is the implementation of a deliberative settlement outside of court. In resolving a traffic accident case that caused serious injuries at the Serang City Police, the perpetrator wanted to resolve it peacefully, through deliberation by providing guarantees to the victim with the aim of restoring the situation. The conclusion of this research is the implementation of restorative justice at the Serang City Police by means of a deliberative settlement outside of court between the perpetrator and the victim or the victim's family so that the perpetrator provides guarantees to restore the victim.